EVALUASI KEBIJAKAN PEMBIAYAAN PENDIDIKAN TINGGI: IMPLIKASI BAGI KESETARAAN SOSIAL - Nordianus WIlfridus; Masduki Ahmad; Heni Rochimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Abstract Higher education is a strategic instrument for promoting social mobility and national development. However, inequality in access due to uneven funding policies poses a serious challenge to achieving social equity. This article evaluates higher education funding policies in Indonesia through a literature review, focusing on BOPTN, KIP-K, and UKT schemes. The findings indicate the persistence of structural and socio-economic barriers that exclude vulnerable groups. Policies have not fully ensured social equity due to disparities in resource distribution, transparency, and implementation effectiveness. Reform grounded in social justice and enhanced monitoring systems is needed. This study contributes to the development of a more inclusive and equitable higher education policy. Keywords: higher education funding, social equity, public policy, education access